Koncepcja zarządzania kosztami wydawnictwa uczelnianego - Kes, Zdzisław; Nowosielski, Krzysztof (The concept of cost management in university publisher, 2008)
In the paper the main guidelines of cost management in a university publisher were presented considering its specificity. The attention was paid to calculation process both ex ante and ex post. The authors proposed multistage implementation process based on the example of one of Wroclaw university publishers. Typical problems in cost budgeting and control in this kind of units were also pointed out.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 141-151